The effect of the hospital working environment on the work limitation of the employees in Turkey: a multivariable analysis - Mahmut Kiliç; Güllü Uslukiliç; Sevda Yaman (BMC, 2023)
Abstract Background The aim of this study is to examine the effects of working environment and demographic variables on the level of work limitation in a university hospital. Methods The study is cross-sectional and was conducted in 2022 among employees of a university hospital. 254 people voluntarily participated in the study. Data were collected by applying the sociodemographic data form, the Work Limitation Questionnaire (WLQ), and the Work Environment Scale (WES). Institutional permission and ethical approval were obtained for the study. In the analysis of the data, t-test, ANOVA, and linear regression (LR) were used. Results The WLQ score average of hospital staff was low. According to LR analysis, the factors affecting the level of work limitation of hospital staff; worsening perception of health status, being a doctor, decreased income level, increased working time in the institution, and age reduction. It was determined that 32.8% of the change in the WLQ score was related to these factors. While in the univariate tests, the mean of work limitation was found to be significant by getting occupational health safety training, having health problems due to the work done, and taking leave due to work accidents, in the multivariable LR analysis, these factors were insignificant. Conclusions As the working environment gets worse, the level of work limitation increases. It is recommended that hospital managers make the working environment better and safer, and make arrangements and programs to increase personnel satisfaction.